The Autoinflammatory Diseases Alliance Registry of monogenic autoinflammatory diseases - Gaggiano, Carla; Vitale, Antonio; Tufan, Abdurrahman; Ragab, Gaafar; Aragona, Emma; Wiesik-Szewczyk, Ewa; Ait-Idir, Djouher; Conti, Giovanni; Iezzi, Ludovica; Maggio, Maria Cristina; Cattalini, Marco; Torre, Francesco La; et al. (Frontiers in Medicine, 2022)
Objective: The present manuscript aims to describe an international, electronic-based, user-friendly and interoperable patient registry for monogenic autoinflammatory diseases (mAIDs), developed in the contest of the Autoinflammatory Disease Alliance (AIDA) Network. Methods: This is an electronic platform, based on the Research Electronic Data Capture (REDCap) tool, used for real-world data collection of demographics, clinical, laboratory, instrumental and socioeconomic data of mAIDs patients. The instrument has flexibility, may change over time based on new scientific acquisitions, and communicate potentially with other similar registries; security, data quality and data governance are corner stones of the platform. Results: AIDA project will share knowledge and expertise on mAIDs. Since its start, 118 centers from 24 countries and 4 continents have joined the AIDA project. Fifty-nine centers have already obtained the approval from their local Ethics Committees. Currently, the platform counts 337 users (122 Principal Investigators, 210 Site Investigators, 2 Lead Investigators, and 3 data managers). The Registry collects baseline and follow-up data using 3748 fields organized into 21 instruments, which include demographics, patient history, symptoms, trigger/risk factors, therapies, and healthcare information for mAIDs patients. Conclusions: The AIDA mAIDs Registry, acts both as a research tool for future collaborative real-life studies on mAIDs and as a service to connect all the figures called to participate. On this basis, the registry is expected to play a pivotal role in generating new scientific evidence on this group of rare diseases, substantially improving the management of patients, and optimizing the impact on the healthcare system. NCT 05200715 available at https://clinicaltrials.gov/.